Associations between perfluoroalkyl substances and lipid profile in a highly exposed young adult population in the Veneto Region. (December 2020) - Canova, Cristina; Barbieri, Giulia; Zare Jeddi, Maryam; Gion, Massimo; Fabricio, Aline; Daprà, Francesca; Russo, Francesca; Fletcher, Tony; Pitter, Gisella
Highlights: Residents of a vast North Italian area were exposed to high concentrations of PFOA. Associations between PFAS and serum lipids were examined in 15, 720 young adults. The shape of exposure-response associations was investigated using smoothing splines. Serum concentrations of PFAS were associated with raised serum cholesterol. The largest increases in cholesterols were seen at the lowest PFAS concentrations. Abstract: Background: Residents of a large area of the Veneto Region (North-Eastern Italy) were exposed for decades to drinking water contaminated by perfluoroalkyl substances (PFAS). PFAS have been consistently associated with raised serum lipids, mainly in cross-sectional studies and in background exposure contexts, but the shape of the dose-response relationships has been poorly investigated. The objectives of our study were to evaluate the association between serum PFAS and serum lipids and their dose-response patterns in a large exposed population. Methods: A cross-sectional study was conducted in 16, 224 individuals aged 20–39 years recruited in the regional health surveillance program. 15, 720 subjects were analysed after excluding pregnant women (n = 327), participants reporting use of cholesterol lowering medications (n = 67) or with missing information on the selected covariates (n = 110). Twelve PFAS were measured by HPLC-MS in serum; three (PFOA, PFOS and PFHxS) were quantifiable in at least 50% of samples. Non-fasting serum total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C) and triglycerides were measured by enzymatic assays in automated analysers and low-density lipoprotein cholesterol (LDL-C), non-HDL cholesterol and total/HDL cholesterol ratio were calculated. The associations between natural log (ln) transformed PFAS and lipids were assessed through generalized additive models using linear regression and smoothing thin plate splines, adjusted for potential confounders. Results: There were strong positive associations between the ln-transformed PFOA, PFOS, and PFHxS and TC, HDL-C, and LDL-C, and between ln PFOA and PFHxS and triglycerides. Each ln-increase in PFOA was associated with an increase of 1.94 mg/dL (95% CI 1.48–2.41) in TC, with 4.99 mg/dL (CI 4.12–5.86) for PFOS and 2.02 mg/dL (CI 1.45–2.58) for PFHxS. Conclusions: Investigation of the shape of exposure-response associations using splines showed a positive association with the largest increases per unit of PFAS in cholesterol levels occurring at the lower range of PFAS concentrations for each compound.